LIZZIE’S OPPRESSION IN SARTRE’S THE RESPECTFUL PROSTITUTE - Aditiya Argo Kusumo (Universitas Katolik Widya Mandala Surabaya, 2015)
Abstract This article discusses about the drama, The Respectful Prostitute, written by Jean-Paul Sartre. It also talks about the oppression experienced by Lizzie in the drama, The Respectful Prostitute, written by Jean-Paul Sartre. This article has two purposes: (1) describe how Lizzie was oppressed in the drama The Respectful Prostitute written by Jean-Paul Sartre, (2) describes the effects experienced by Lizzie after the persecution. This article uses the theory of feminism, radical feminism and woman oppression, while the approaches are the psychological approach and sociological approach. This analysis proves that Lizzie had been oppressed by white people, namely: Fred, Thomas, and Senator. This is proved when Lizzie suffered physical violence such as rape trials conducted by Fred and Thomas. Second, when Lizzie was forced to sign a letter that contains a false statement that Thomas did not kill The Negro. Â Key Words: Woman oppression, Radical feminism, Feminism